PERAN GEL LIDAH BUAYA DALAM MENGURANGI XEROSIS - Khoirini, Fatimah (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
The management of patients with Chronic Renal Failure (CRF) is theimmediate treatment of the infection to prevent infection to the patient's kidney due todecreased immunity. CRF patients almost all have dermatological disorders, includingxerosis. Pharmacological treatment causes a lot of side effects. One natural ingredient isaloe vera. Aloe vera as a moisturizer, antibiotics and as well itching. This study aims toanalyze the effectiveness of aloe vera gel as a material alternative to nursingimplementations in xerosis CRF patients in Semarang hospitals. This type of research isexperiment with using pretest posttest control group design, selection sampling withrandom sampling taking random table. The number of respondents 36 people, that are 18people giving the control group a placebo gel skin lotion 2 times daily after bath for 3days and 18 people experimental group with the administration of aloe gel 2 times dailyafter bath for 3 days. Observations using Akhyani modifications observation sheet.Xerosis difference in the two groups were analyzed by paired samples T-test, while therelationship with the respondent characteristics xerosis is analyzed by independentsample T-test and corelations. Statistical test results showed no significant differencexerosis before and after administration of aloe vera gel with xerosis value (p =0.000).The implication of this study is the Aloe vera gel can be considered to bealternatives to nursing implementations xerosis patients with CRF.